2017
DOI: 10.2196/preprints.9082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding a Nonlinear Causal Relationship Between Rewards and Physicians� Contributions in Online Health Care Communities: Longitudinal Study (Preprint)

Abstract: Background: The online health-care community (OHC) is not just a place for the public to share physician reviews or medical knowledge; it is also a physician-patient communication platform. The medical resources of developing countries are relatively inadequate, and the OHC is a potential solution to alleviate the phenomenon of long hospital queues and the lack of medical resources in rural areas. However, the success of the OHC depends on online contributions by physicians. Objective: The aim of this study is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Some researchers have analyzed and confirmed that social media can promote tacit knowledge sharing among doctors. Doctors are willing to acquire and share knowledge and establish trust with others through social media [6] . Wang et al [7] analyzed the knowledge-sharing behavior of doctors in online medical platforms and found that the material needs of doctors for knowledge sharing are more fundamental than their psychological needs, which is consistent with the analysis of Maslow's theory.…”
Section: Doctors' Behavior In Online Medical Platformsmentioning
confidence: 99%
“…Some researchers have analyzed and confirmed that social media can promote tacit knowledge sharing among doctors. Doctors are willing to acquire and share knowledge and establish trust with others through social media [6] . Wang et al [7] analyzed the knowledge-sharing behavior of doctors in online medical platforms and found that the material needs of doctors for knowledge sharing are more fundamental than their psychological needs, which is consistent with the analysis of Maslow's theory.…”
Section: Doctors' Behavior In Online Medical Platformsmentioning
confidence: 99%